PENGGUNAAN PERINTAH SUARA UNTUK PENGONTROLAN PERGERAKAN WIPER PADA MOBIL LISTRIK - Rizkia Meilani; Fajri; Eko Sulistyo; Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Controlling equipment using voice commands is still not widely applied to electric cars. Generally, electric car equipment is still mostly controlled electrically. To optimize the control of this equipment, it is necessary to develop control via voice commands via smartphones. The purpose of controlling equipment using voice commands is to increase the ease and safety of users in controlling electric car equipment. The methodology used in this research involves changing voice commands through the speech recognizer contained in the SKMML application that has been developed and testing the response of electric car equipment when given a voice command based on a predetermined command code. From the test results, when the wiper electric car equipment is given a voice command, the percentage of success is 100% in the no-noise condition and the success percentage is 96% in the noise-inducing condition, with a duration of response to the voice command of 4 seconds. The failure of the tool response is due to poor articulation and intonation of voice commands, which makes it difficult for the speech recognizer to recognize voice commands that have been spoken.